2023
DOI: 10.2147/opth.s398990
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of Maladaptive Coping Strategy and Its Associated Factors Among Adult Glaucoma Patients Attending Tertiary Eye Care Center in Ethiopia

Abstract: Introduction Coping strategy is the mechanism by which patients adjust to the condition they face. It can be adaptive or maladaptive. A maladaptive coping strategy is a harmful and ineffective way of dealing with stress or anxiety. It is common among patients with chronic illnesses. Despite Ethiopia having a greater glaucoma prevalence, there was no evidence of patients with glaucoma using maladaptive coping mechanisms. Objective The main goal of this study was to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Additionally, addressing the stigma associated with vision loss and mental health issues, the constraint of time during medical appointments, limited access to mental health services, and the need for effective coping strategies further complicate the provision of comprehensive care. Birhan et al [ 54 ] conducted a cross-sectional study involving 423 glaucoma patients, revealing that 50.1% (95%CI: 45.1%-54.5%) of the surveyed individuals employed maladaptive coping strategies, potentially exacerbating mental health challenges. Conversely, Zhou et al [ 55 ] found a connection between improved mental health regulation and better self-management behavior in glaucoma patients in China.…”
Section: Integrated Approaches To Glaucoma Care: Implications On Mana...mentioning
confidence: 99%
“…Additionally, addressing the stigma associated with vision loss and mental health issues, the constraint of time during medical appointments, limited access to mental health services, and the need for effective coping strategies further complicate the provision of comprehensive care. Birhan et al [ 54 ] conducted a cross-sectional study involving 423 glaucoma patients, revealing that 50.1% (95%CI: 45.1%-54.5%) of the surveyed individuals employed maladaptive coping strategies, potentially exacerbating mental health challenges. Conversely, Zhou et al [ 55 ] found a connection between improved mental health regulation and better self-management behavior in glaucoma patients in China.…”
Section: Integrated Approaches To Glaucoma Care: Implications On Mana...mentioning
confidence: 99%